RELIGIOUS LANDSCAPE, LOW CASTE HINDUS AND THE IDENTITY POLITICS: CONFIGURATION OF SOCIO-RELIGIOUS SPACE FOR WEAKER SECTIONS IN JAMMU CITY, J&K (INDIA) - Saxena, Ashish (Politikologija religije, 2013)
Dawning of a new century has not been accompanied by the eclipse of religiosity among individuals and in public culture rather because of disenchantment with our increasingly rationalized society, religion continues to provide meaning and intertwine daily social, economic, and political activity of human world. Alongside, the popular religiosity is an important contemporary trend encompassing the world religions. The study of religion as a force in people’s adaptation to and creation of landscape is certainly a proper and important endeavor in the field of sociology of religion. The present work aims at exploring the spatial expansion of subaltern groups in urban setting; socio-religious mobility among lower caste Hindus and the creation of sacred and secular space vis-à-vis higher Hindu caste groups in a sacred traditional Indian city. The broader findings reflect the creation of religious spaces and also the lower caste Hindu identity assertion through these places. The modern forces and the pace of urbanization had diluted the air-tight compartmentalized segregation of the weaker section and paved them way for secular living with the other high caste groups. It had not only brought democratic dwelling space but also provided them dignity with the new level of assertion.